Territorial competition and personal quality of candidates. A presidential elections analysis in Mexico between 2006 and 2018. (2020)
This research project presents a spatial competition model for Mexican presidential elections based on the effective number of parties and weighted and scalar polarization indices. The model makes it possible to construct a classification of candidates influences based on personality as an remainder unexplained by spatial ideological competition. In addition to classifying the candidates in the last three presidential elections by their personal influence, the authors offer predictions for future balloting based on change in ideological distribution. Suppositions of symmetrical ideological votes and a single dimension were used to build the model.